Oral Immunization with Nontoxigenic Clostridium difficile Strains Expressing Chimeric Fragments of TcdA and TcdB Elicits Protective Immunity against C. difficile Infection in Both Mice and Hamsters - Wang, Yuanguo (Infect Immun, 2018)
The symptoms of Clostridium difficile infection (CDI) are attributed largely to two C. difficile toxins, TcdA and TcdB. Significant efforts have been devoted to developing vaccines targeting both toxins through parenteral immunization routes. However, C. difficile is an enteric pathogen, and mucosal/oral immunization would be particularly useful to protect the host against CDI, considering that the gut is the main site of disease onset and progression. Moreover, vaccines directed only against toxins do not target the cells and spores that transmit the disease. Previously, we constructed a chimeric vaccine candidate, mTcd138, comprised of the glucosyltransferase and cysteine proteinase domains of TcdB and the receptor binding domain of TcdA. In this study, to develop an oral vaccine that can target both C. difficile toxins and colonization/adhesion factors, we expressed mTcd138 in a nontoxigenic C. difficile (NTCD) strain, resulting in strain NTCD_mTcd138. Oral immunization with spores of NTCD_mTcd138 provided mice full protection against infection with a hypervirulent C. difficile strain, UK6 (ribotype 027). The protective strength and efficacy of NTCD_mTcd138 were further evaluated in the acute CDI hamster model. Oral immunization with spores of NTCD_mTcd138 also provided hamsters significant protection against infection with 2 × 10(4) UK6 spores, a dose 200-fold higher than the lethal dose of UK6 in hamsters. These results imply that the genetically modified, nontoxigenic C. difficile strain expressing mTcd138 may represent a novel mucosal vaccine candidate against CDI.